2020
DOI: 10.1029/2019jd032184
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Higher Spatial Atmospheric Resolution on Precipitation Extremes Over Land in Global Climate Models

Abstract: Finer grids in global climate models could lead to an improvement in the simulation of precipitation extremes. We assess the influence on model performance of increasing spatial resolution by evaluating pairs of high‐ and low‐resolution forced atmospheric simulations from six global climate models (generally the latest CMIP6 version) on a common 1° × 1° grid. The differences in tuning between the lower and higher resolution versions are as limited as possible, which allows the influence of higher resolution to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
67
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 57 publications
16
67
0
Order By: Relevance
“…For wind, Willison et al (2015) find a larger response of the North Atlantic storm track to global warming with higher resolution in the regional WRF model. Furthermore, Baker et al (2019) find that in winter the polar jet, storm tracks, and associated precipitation shift further north over the Euro-Atlantic region in the future with increased resolution in the same HadGEM3-A set-up as used here. The sensitivity of projections to resolution nevertheless remains an area that needs further research.…”
Section: Discussionmentioning
confidence: 69%
“…For wind, Willison et al (2015) find a larger response of the North Atlantic storm track to global warming with higher resolution in the regional WRF model. Furthermore, Baker et al (2019) find that in winter the polar jet, storm tracks, and associated precipitation shift further north over the Euro-Atlantic region in the future with increased resolution in the same HadGEM3-A set-up as used here. The sensitivity of projections to resolution nevertheless remains an area that needs further research.…”
Section: Discussionmentioning
confidence: 69%
“…Because core precipitation occurs over a small area, it relates more directly to extreme precipitation metrics defined at the gridpoint scale than precipitation averaged in the whole tropical cyclone does. Interestingly, Bador et al (2020) found that HadGEM3-GC3.1 and CMCC-CM2 produce the largest change with resolution of the following extreme precipitation metrics: maximum 1-day precipitation (rx1day), maximum 5-day precipitation (rx5day), and total precipitation from extremely wet days (r99p), over both land and ocean, suggesting that tropical cyclone core precipitation in these models share essential physics with processes that contribute to set the extreme precipitation captured by those three metrics.…”
Section: B Tropical Cyclone Core Precipitationmentioning
confidence: 99%
“…This suggests that the models overestimate the correlation between precipitation and wind. Nevertheless, given previous assessments that found CMIP6 models simulate heavy rainfall relatively poorly (Bador et al., 2020; Kim et al., 2020) and the relative lack of analyses of strong winds, many CMIP6 models capture WP‐CEs surprisingly well. However, there are areas where individual models fail to reflect the observations well.…”
Section: Resultsmentioning
confidence: 99%
“…(2013) note that CMIP5 models generally capture observed trends in temperature extremes, but rainfall extremes are more challenging, although this might be partly due to higher observational uncertainty. Since this assessment, extensive literature has emerged demonstrating the improved skill of climate models in simulating temperature (e.g., Di Luca et al., 2020) and rainfall extremes (Bador et al., 2020), particularly in hot and cold extremes (Di Luca et al., 2020) and the intensity of heavy rainfall (Kim et al., 2020). The evaluation of wind extremes is more limited, but Kumar et al.…”
Section: Introductionmentioning
confidence: 99%